Funerals in Africa : Explorations of a Social Phenomenon. - Jindra, Michael (Berghahn Books, 2011)
This collection is of great benefit to scholars and students across a wide range of disciplines, including anthropology, sociology, development studies, economics, history, religious studies. REBEKAH LEE, University of London. Funerals in Africa is an excellent volume. Based on outstanding original research the collection shows how social and economic changes in Africa are illuminated through the analysis of burials, mortuary rites, mourning, and remembrance. In this collection encounters with world religions emerge as the key theme. Death and burial are therefore employed to illuminate classi.